KEWIRAUSAHAAN BAGI ISTRI KARYAWAN KONTRAK HOTEL UMM INN - Setyawan, Setu (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2016)
Every man has an entrepreneurialspirit, it relates to the nature of subsistence,the potential of entrepreneurship must be explored. Entrepreneurship is the spirit, behavior and the ability to respond positivelyto the opportunity to benefit themselves or abetter service, as well as create and provideproducts that are more useful and implementways of working efficiently, through thecourage to take risks, creativity and innovation, and ability management (Eko. 2013).Most people perceive that entrepreneurship is the last alternative an option tomeet the standards of living, most becameemployees of private institutions (enterprises) and the government becomes theprimary choice. Indeed, if viewed from therisk experienced between entrepreneurs bybecoming more worker-risk being an entrepreneur, an employee's income is definitelythe number and time of receipt no changewithin a certain period, while self-employment has a chance to make more money andbe able to provide job opportunities topeople other. There are some things thatunderlie this important programimplemented first, provide basic knowledgeand skills of entrepreneurship, Both providebasic skills to make various flavors of drinkscappuccino seabagai initial capital to start abusiness at home or in public places atcertain events that invite the public, the thirdadd family income.Resources or target group indevotion is the wife of UMM Inn Dhaniel Syam Fakultas Ekonomi Dan Bisnis UMMHotel contract employees who do not haveformal jobs, in addition to her husband's incomeas well as a contract employee UMM Inn hotelaverage Rp. 1,400,000 per month, the income isnot enough to sustain the cost of living for thefamily, therefore she must be trickedberwiarausaha the small home to supplementher husband's income. Based on the data on thenumber of employees as many as 43 people,consisting of 31 men and 11 women, almost 80%of his wives do not work.